OP0119 Patient Journey and Treatment Route to Use of First Biologic in Rare Autoinflammatory Diseases: an International Retrospective Chart Review. (10th June 2014) - Özen, S.; Kuemmerle-Deschner, J.; Cantarini, L.; Cimaz, R.; Quartier, P.; Gül, A.; Koné-Paut, I.; Spalding, S.; Zeft, A.; Simon, A.; Hashkes, P.; Hentgen, V.; et al.
Abstract : Background: Due to low incidence rates, treatment data and guidelines in hereditary periodic fevers are limited. To complement published data from the autoinflammatory diseases PRINTO/Eurofever registry, an international noninterventional study of colchicine-resistant familial Mediterranean fever (crFMF), tumor necrosis factor-receptor-associated periodic syndrome (TRAPS), or hyperimmunoglobulinemia D with periodic fever syndrome (HIDS) patients was conducted. Objectives: To characterize the patient journey from disease onset to 1st use/eligibility of a biologic. Methods: Chart review of adult/pediatric patients with clinically or genetically confirmed disease treated by a specialist (2008-12), with ≥12-mo follow-up post diagnosis. Eligible patients had inadequate response/intolerance to 1st-line treatment and received/were eligible for biologics. Eligible FMF patients had an inadequate response to colchicine as determined by physician (termed crFMF). Results: 54 crFMF, 47 TRAPS and 38 HIDs patient records were analyzed. Time from symptom onset to diagnosis: 3.5-12.7 years. Only 33% and 46% of TRAPS and HIDS patients, respectively, received correct diagnosis before expert referral vs 69% with crFMF. Median times from disease onset to initiation of 1st biologic: 6.1 (crFMF), 5.9 (TRAPS) and 1.4 (HIDS) years. Initial and subsequent treatment as provided by specialists is reported here. All crFMF patients received colchicine: 6% subsequently had complete response (CR), 65% partial response (PR) and 29% no response (NR); 31 received 1st biologic plus colchicine (the 3 CR patients were deemed eligible by physician for a biologic due to CR loss, high colchicine dose, or continued severe symptoms). Of 47 TRAPS patients, initially 26 received a biologic; 21, corticosteroids. Of patients on corticosteroids, 34%, 42%, and 24% had CR, PR, and NR, respectively; 3 patients continued and 1 discontinued corticosteroids, and 17 switched to 1st biologic. Of 38 HIDS patients, initially 25 patients received a biologic (with 4 awaiting biologic) and 9 corticosteroids. Of patients on corticosteroids, 11%, 67% and 22% had CR, PR and NR, respectively; 3 patients continued and 6 switched to 1st biologic. Conclusions: This analysis supports the need for greater awareness of such diseases, expedited referral to specialized centers, and development of standardized treatment algorithms, definitions of response, and guidelines. Disclosure of Interest: S. Özen Consultant for: Novartis, Speakers bureau: Biovitrium-SOBI, Novartis, J. Kuemmerle-Deschner Consultant for: Novartis, L. Cantarini Grant/research support: Novartis, SOBI, Consultant for: Novartis, SOBI, R. Cimaz: None declared, P. Quartier Grant/research support: Abbvie, BMS, Chugai-Roche, Novartis, Pfizer, SOBI, Consultant for: Abbvie, Chugai-Roche, Novartis, Pfizer, Servier, SOBI, Speakers bureau: Chugai-Roche, MEDIMMUNE, Novartis, Pfizer, A. Gül Grant/research support: Novartis, Consultant for: Novartis, Speakers bureau: Novartis, I. Koné-Paut Grant/research support: SOBI, LFB, Consultant for: Novartis, SOBI, Pfizer, Chugai, S. Spalding: None declared, A. Zeft Consultant for: Novartis, A. Simon Grant/research support: Servier, Consultant for: Novartis, Servier, SOBI, P. Hashkes Grant/research support: Novartis, Consultant for: Novartis, Paid instructor for: Novartis, V. Hentgen Consultant for: Novartis, Paid instructor for: Novartis, Pfizer, Roche, T. Kallinich Speakers bureau: Novartis, Pfizer, S. Savic Consultant for: Novartis, I. Foeldvari Consultant for: Novartis, Abbott, Chugai, Genzyme, J. Frenkel Grant/research support: European Union ERANET, Consultant for: Novartis, U. Machein Employee of: Novartis, A. Livneh: None declared, H. Lachmann Grant/research support: Novartis, Celtic, Consultant for: Novartis DOI: 10.1136/annrheumdis-2014-eular.3251